Bowel infarct with mucormycosis of the intestine - Sangal, Bharat; Sharma, Rajeev; Joseph, Molly; Chatterjee, Debarghya (International Surgery Journal, 2019)
Gastrointestinal mucormycosis is a relatively uncommon opportunistic fungal infection. The classical presentation is that of a rhino-cerebral infection. It is a life threatening, angio-invasive condition typically affecting immunocompromised individuals. Only a handful cases of intestinal mucormycosis have been reported to date. Here, we discuss our experience regarding an adult male patient who succumbed to bowel infarction and perforation with septic shock due to intestinal mucormycosis.